THE IMPACT OF ORGANIZATIONAL CULTURE AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE IN BALI’S HOSPITALITY INDUSTRY - Yani, Ni Wayan Merry Nirmala; Sri Astuti, Ni Nyoman; Virginiya, Putu Tika; Bagiastuti, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to examine the relationship between organizational culture, employee engagement, and employee performance, and explore the mediating role of employee engagement in the relationship between organizational culture and employee performance. The study's main instrument for collecting information was a questionnaire, and a sample of Bali hotel staff members was chosen via simple random sampling. Data were analyzed using first-order path analysis with structural equation modelling (SEM) in SmartPLS software. The findings showed that employee engagement and performance are significantly improved by company culture; employee performance is dramatically enhanced by employee engagement. Furthermore, employee performance and company culture are mediated in a complementary way by employee engagement. Organizational culture greatly improves employee engagement, thus positively impacting employee performance. By offering fresh perspectives on the connections among corporate culture, employee engagement, and employee performance, this study advances the Social Exchange Theory (SET). The findings support the SET principles by showing how organizational culture affects employee engagement and performance in the hotel sector.